Just transition for waste pickers in the global plastics treaty: what is it and why is it important? - Patrick O’Hare; Taylor Cass Talbott (Cambridge Prisms: Plastics)
This letter to the editor explores the importance of a just transition for waste pickers in the context of the global plastics treaty. It sets out ideas for just transition at the level of production reduction, replacements and substitutes, systems change and waste management.